2012
DOI: 10.4244/eijv8i1a9
|View full text |Cite
|
Sign up to set email alerts
|

First-in-man experience with a new embolic deflection device in transcatheter aortic valve interventions

Abstract: In this first-in-man experience, the feasibility of a new embolic deflection device is demonstrated. Larger randomised, prospective studies are required to confirm these findings and prove safety and efficacy by reducing the incidence of cerebral embolism and stroke after TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 15 publications
1
43
0
1
Order By: Relevance
“…In our cases clopidogrel and warfarin was given for one month for the INR to be 2.0-2.5, and only warfarin treatment was applied after a month. Additionally new emboli protecting devices are being developed (e. g., Embrella [Edwards Lifesciences, Inc., Irvine, CA, USA], Claret [Claret Medical, Inc. Santa Rosa, CA, USA], SMT Embolic Deflection Device) in order to prevent process related emboli and the human studies regarding these are promising [12]. As far as we know no TAVI case is found for patients with AF and thrombus in LAA in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our cases clopidogrel and warfarin was given for one month for the INR to be 2.0-2.5, and only warfarin treatment was applied after a month. Additionally new emboli protecting devices are being developed (e. g., Embrella [Edwards Lifesciences, Inc., Irvine, CA, USA], Claret [Claret Medical, Inc. Santa Rosa, CA, USA], SMT Embolic Deflection Device) in order to prevent process related emboli and the human studies regarding these are promising [12]. As far as we know no TAVI case is found for patients with AF and thrombus in LAA in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Age, hypertension, diabetes, calcified ascending aorta, female gender, story of stroke, AF and the degree of the atheroma plates in the aortic arch are included in the risk factors for emboli [6,12]. New AF related to TAVI which causes an increase in post procedural stroke risk for 3.9 times was determined to be 7.5% in the transfemoral arm, 11.5% in the transapical arm of cohort A, and 0.7% in cohort B of PARTNER [3,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMT FIM (first in man) feasibility study described the use of the SHEF device in the first 15 patients. 62 The ongoing DEFLECT I (SMT Embolic Deflection CE Mark) study is expected to provide further evidence of the effectiveness of the device. First results have been presented at EuroPCR in May 2013 in Paris and show promising results.…”
Section: Renalna Denervacijamentioning
confidence: 99%
“…The uses of aortic flow deflectors and cerebral protection devices is an appealing concept which has been tested in some preliminary clinical studies which have not yet confirmed the effectiveness of these devices [29,30].…”
mentioning
confidence: 99%